2022
DOI: 10.1371/journal.pone.0266141
|View full text |Cite
|
Sign up to set email alerts
|

Women’s health status before and during the COVID-19 pandemic in rural Bangladesh: A prospective longitudinal study

Abstract: The coronavirus disease (COVID-19) pandemic has widely spread worldwide since 2020. Several countries have imposed lockdown or stay-at-home policies to prevent the infection. Bangladesh experienced a lockdown from March 2020 to May 2020, and internal travel was restricted. Such long and strict confinement may impact women’s health. Herein, we aimed to assess the impact of the COVID-19 pandemic on women’s health by comparing their health status before and during the pandemic. We conducted a prospective longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…It was obvious that individuals became less active due to the preventive measures against SARS-CoV-2 transmission during the COVID-19 pandemic (15,16). Consistent with our findings, similar results were reported that SBP, DBP, and BMI during the pandemic were significantly increased in women's health checkups in Bangladesh (17). Incidentally, the frequency of antihypertensive medication use did not significantly increase during the COVID-19 pandemic in this study, as patients with hypertension may have become more reluctant to visit clinics because of the risk of COVID-19 infection in the early stage of the pandemic, although people may have paid more attention to their health conditions because comorbidity of hypertension (18), diabetes (19), heart disease (20,21), hepatic cirrhosis (22), obesity (23), chronic kidney disease (24), cancer (25) and chronic obstructive pulmonary disease (26) may be associated with more severe COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…It was obvious that individuals became less active due to the preventive measures against SARS-CoV-2 transmission during the COVID-19 pandemic (15,16). Consistent with our findings, similar results were reported that SBP, DBP, and BMI during the pandemic were significantly increased in women's health checkups in Bangladesh (17). Incidentally, the frequency of antihypertensive medication use did not significantly increase during the COVID-19 pandemic in this study, as patients with hypertension may have become more reluctant to visit clinics because of the risk of COVID-19 infection in the early stage of the pandemic, although people may have paid more attention to their health conditions because comorbidity of hypertension (18), diabetes (19), heart disease (20,21), hepatic cirrhosis (22), obesity (23), chronic kidney disease (24), cancer (25) and chronic obstructive pulmonary disease (26) may be associated with more severe COVID-19 outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…These findings align with several studies conducted during the pandemic in quarantine periods, showing that people experienced the worst level of health, especially women. The lower access to medical checkups, the changes in diet due to confinement and lower access to healthy food, and the high sedentary lifestyle and low level of physical activity could explain this worst level of health in women [21,55]. In our study, a negative perception of mental and general health status was also associated with a worse perception of domestic work.…”
Section: Discussionmentioning
confidence: 47%
“…This also increases the risk of causing deterioration in women's physical and mental health [17][18][19]. Data showed that women had a higher level of stress than men [20], and compared to the pre-pandemic period, during the pandemic, they could increase their BMI and blood pressure [21]. This way, the pandemic crisis and women's responsibilities could also affect their general wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…This study considers the Portable Health Clinic (PHC) system as a reference telehealth service that uses this kind of portable sensor (Figure 1) [6][7]. It considers the portability, price, and usability of the sensors as the major criteria for selecting sensors.…”
Section: Introductionmentioning
confidence: 99%